2020
DOI: 10.1186/s12884-020-2757-x
|View full text |Cite
|
Sign up to set email alerts
|

Respectful maternity care and associated factors among women who delivered at Harar hospitals, eastern Ethiopia: a cross-sectional study

Abstract: Background: In Ethiopia, approximately three-fourths of mothers do not deliver in health facilities. Disrespect and abuse during childbirth fallouts in underutilization of institutional delivery that upshots maternal morbidity and mortality. Thus, the ambition of this study was to assess respectful maternity care and associated factors in Harar hospitals, Eastern Ethiopia. Methods: A facility-based cross-sectional study was conducted from April 01 to July 01, 2017. A total of 425 women, delivered at Harar town… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 27 publications
(37 reference statements)
8
49
6
Order By: Relevance
“…Physical abuse during childbirth was reported in eighteen of the cross-sectional and qualitative studies [ 14 , 31 37 , 39 – 45 , 49 51 ] and ranged from 9% to 87.9%. To include, being beaten, slapped, and/or pinched by the health care provider [ 14 , 31 , 33 37 , 39 , 41 , 44 , 45 , 48 51 ] and care providers used force to push the abdomen down (used fundal pressure) to deliver their babies [ 32 , 40 , 45 ], episiotomy done or perineum sutured without antipain (anesthesia) [ 39 , 43 , 45 ], restrained or tied down during labor [ 36 , 40 ], legs apart harshly and forcefully during labor were reported in 33.8% [ 36 ] and 13.9% [ 50 ] of them, 1.8% faced previous experience of sexual abuse by the caregiver [ 37 ], and a qualitative studies have argued that painful per-vaginal exam have been carried out multiple times without notifying the findings [ 34 , 42 ]; “The caregivers have psychologically wounded us, They have come and did vaginal exams repeatedly as easy as anything but it is a huge trauma to us” [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical abuse during childbirth was reported in eighteen of the cross-sectional and qualitative studies [ 14 , 31 37 , 39 – 45 , 49 51 ] and ranged from 9% to 87.9%. To include, being beaten, slapped, and/or pinched by the health care provider [ 14 , 31 , 33 37 , 39 , 41 , 44 , 45 , 48 51 ] and care providers used force to push the abdomen down (used fundal pressure) to deliver their babies [ 32 , 40 , 45 ], episiotomy done or perineum sutured without antipain (anesthesia) [ 39 , 43 , 45 ], restrained or tied down during labor [ 36 , 40 ], legs apart harshly and forcefully during labor were reported in 33.8% [ 36 ] and 13.9% [ 50 ] of them, 1.8% faced previous experience of sexual abuse by the caregiver [ 37 ], and a qualitative studies have argued that painful per-vaginal exam have been carried out multiple times without notifying the findings [ 34 , 42 ]; “The caregivers have psychologically wounded us, They have come and did vaginal exams repeatedly as easy as anything but it is a huge trauma to us” [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…They made negative comments and mocking [ 32 , 34 , 44 ] …“Some of them heap scorn on you when you are in labor” [ 34 ]. Unfriendly, unwelcomed, and impolite approaches of health care providers were found in seven of cross-sectional studies [ 14 , 32 , 38 , 43 , 45 , 48 , 51 ]. In a qualitative study done on women who gave birth at home and who had previous experience of facility-based childbirth, one woman stated, “The traditional birth attendants will take care of your feelings; they treat you with sympathy.…”
Section: Resultsmentioning
confidence: 99%
“…Respectful care: was measured by four performance standards (friendly care, timely care, discrimination-free care, and abuse-free care). 12 In each performance standard, there were Likert type items to measure each category. During analysis, the responses of “strongly agree” and “agree” were classified as “Yes” (received RMC), and the responses of “strongly disagree”, “disagree” and “neutral” were classified as “No” (disrespected and abused) for positive statements for each standard.…”
Section: Methodsmentioning
confidence: 99%
“…25 Similarly, studies in different parts of Ethiopia on the issue reported a high prevalence, ranging from 36-98.9%. 2,[26][27][28][29][30] Disrespect and abuse are universal maternal health care utilization problems. However, it is unspoken that has been attributed to courtesy bias where women do not tend to report D&A while still in the health facility.…”
Section: Introductionmentioning
confidence: 99%